2008
DOI: 10.1021/ja710126x
|View full text |Cite
|
Sign up to set email alerts
|

Mild, Rhodium-Catalyzed Intramolecular Hydroamination of Unactivated Terminal and Internal Alkenes with Primary and Secondary Amines

Abstract: The hydroamination of olefins 1 is one of the simplest and most atom-economical methods to prepare alkylamines, and much effort has now been spent to develop catalysts for this process. Some of most reactive catalysts contain lanthanides 2 and group IV transition metals. 3 However, the high sensitivity of these catalysts toward air and moisture and their low tolerance of polar functional groups have limited their use and motivated efforts to develop late-metal hydroamination catalysts. Although several cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(82 citation statements)
references
References 42 publications
6
76
0
Order By: Relevance
“…A second set of experiments were run in the presence of 10 mol % added COD, which is present in the catalyst precursor and was present in our preparative reactions of secondary aminoalkenes initiated with isolated acetonitrile complex 2 27. The added COD appeared to stabilize the catalyst, but to retard the cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…A second set of experiments were run in the presence of 10 mol % added COD, which is present in the catalyst precursor and was present in our preparative reactions of secondary aminoalkenes initiated with isolated acetonitrile complex 2 27. The added COD appeared to stabilize the catalyst, but to retard the cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…Although data with this original catalyst35 and that with catalysts based on copper,34 rhodium,37 and iridium40,46 reported since this time demonstrated that primary aminoalkenes can undergo cyclization, reactions of such such amines catalyzed by these systems have significant limitations. First, the cyclization of primary aminoalkenes catalyzed by late-metal systems has been limited to cases that are biased toward cyclization by a Thorpe-Ingold effect; second, these reactions were limited to aminoalkenes containing terminal olefins; third, these reactions required high temperatures (>100 °C); and fourth, reactions of primary aminolkenes containing a second functional group have not been reported with any catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, ligated rhodium complexes have been developed as catalysts for the intramolecular hydroamination of unactivated aminoalkenes containing a basic amine functionality [40]. In particular, rhodium complexes have been the first class of catalysts to demonstrate reactivity with substrates that contain a primary amine donor [41], and also tolerate a wide range of polar functionality. The most effective catalysts to date are monocationic at the rhodium center and are proposed to react via the nucleophilic addition pathway (Scheme 3).…”
Section: Rhodium-catalyzed Reactionsmentioning
confidence: 99%
“…Hartwig and Liu subsequently reported a rhodium catalyst bearing the Davephos ligand that exhibits excellent activity for hydroamination of unactivated alkenes containing both primary and secondary amines (Scheme 24) [41]. Substituted aminoalkenes containing a wide range of functionality, such as aryl nitriles, esters, and alcohols (53, Ar ¼ 4-ClC 6 H 4 , 4-CNC 6 H 4 , 4-CO 2 MeC 6 H 4 ), were cyclized at relatively mild temperatures to form pyrrolidines and piperidines selectively.…”
Section: Rhodium-catalyzed Reactionsmentioning
confidence: 99%